(untitled) (Journal SCIENCEVOLUTION, 2025)
Currently, the interpretative task of fundamental rights of a positive nature within constitutional provisions gives rise to various norms, some of which conflict with the foundations of conservative societies. Consequently, this study aims to analyze the limits of activist interpretation of fundamental rights in societies with conservative legal systems. For its development, the dogmatic method was employed under a qualitative approach, through doctrinal and jurisprudential analysis. The results indicate that legal activism has a significant impact on the interpretation of fundamental rights in conservative legal systems, demonstrating that it redefines their interpretation to adapt to new social demands. Additionally, six limits to activist interpretation of fundamental rights were identified from moral, constitutional, democratic, common good, and jurisprudential perspectives. These elements establish a framework within which judges can operate without compromising institutional balance or the traditional values of a society governed by conservative law.